Implementasi Art Journaling Untuk Mengeksplorasi Ekspresi Diri Siswa Kelas V Sekolah Dasar - Sadiah, Rahma; Melsya Fitrikasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of art journaling in art education and to analyze the improvement of self-expression exploration among fifth-grade elementary students. The research employed a descriptive qualitative approach involving 35 students and one teacher at SD Negeri 03 Bojonglongok. Data were colected through observation, semi structured interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings revealed that initial learning tended to be product oriented and relied on modeling, which limited students’ ideas and self-expression. The implementation of art journaling increased students’ engagement, confidence, and ability to develop ideas based on personal experiences through a combination of drawings and writing. Students’ artworks became more diverse in terms of themes, colors, and media. In conclusion, art journaling is an effective alternative approach in art education that is reflective, personal, and student-centered. This study contributes to the development of expressive learning strategies in elementary education, although it is limited by the research context and number of participants.